Current and echo backscatter measurements on the Laptev Sea shelf in 2013-2014 at mooring site Vilkitzky-13 - Jens A Hölemann; Markus A Janout; Leonid Timokhov; Heidemarie Kassens (PANGAEA, 2024)
The Vilkitzky-13 mooring was deployed in September 2013 at a water depth of 320 m in the ~250 km-long submarine extquotesingleVilkitzky Trough extquotesingle in the seasonally ice-covered Laptev Sea (Siberian Arctic) and recovered in September 2014. The location of the mooring is characterized by the transport of water masses from the shallow shelf of the Kara and Laptev Seas to the Arctic boundary current. The 291-m-long mooring was equipped with RDI-Workhorse ADCPs for current measurements and Seabird SBE37 CTDs for temperature and salinity measurements (doi.org/10.1594/PANGAEA.924043). The current was recorded at intervals of 2 m (300 kHz ADCP, 5 to 25 m water depth) and 5 m depth (150 kHz ADCP, 46 to 171 m water depth). The measurement interval was 1 hour. The ADCP current measurements were corrected for declination. The declination was calculated using the Enhanced Magnetic Model (EMM2017 on NOAA.gov.). Due to erroneous measurements caused by a technical problem, the data from the 150 kHz ADCP recorded between the seabed and a water depth of 176 m were discarded. A total of four moorings (1893, Taymyr, Kotelny, Vilkitsky) were deployed on the shelf of the Laptev Sea in September 2013 during the Transdrift 21 expedition and recovered in September 2014 during Transdrift 22 on board the research vessel Viktor Buinitsky (doi.org/10.1594/PANGAEA.908837). The expeditions were carried out as part of the German-Russian partnership Laptev Sea Systems and the BMBF-funded Transdrift project.